The twilight of education? Reflections on the concept of cyborgization - Klichowski, Michał (theQ studio, 2015)
The article presents the basic assumptions of the abovementioned philosophies, constitutive points of reference for the idea of cyborgization (new eugenics and transhumanism). It also highlights how education might be perceived in relation to these ideas. I believe such a presentation to be important. As it was already mentioned, the concept of cyborgization revolutionizes our thinking about the core of humanity. On the other hand, it is the foundation for another idea: the twilight of education, or irrelevance of traditionally understood education in the technoworld. Twilight of education is a certain regularity of reflection about the role of education in human technological progress. It is an orderly method of looking at the future of the relation between humans and education. This regularity and order are rarely expressed explicitly; instead, we encounter them implicitly. Explicitly means here that some texts in the field of new eugenics and transhumanism speak directly about how certain technological activities replace education as more effective measures. Implicitly, in turn, means that such texts present detailed strategies for stimulation of human progress but completely ignore educational influences. All types of stimulants are of technical nature. Analyses of the concept of cyborgization result in a prediction for the future: the traditionally educational activities shall somehow disappear from the ‘cyborgized society’, even though such a society still remains only a hypothesis. Thus the twilight of education mentioned in the title of this paper will become true.
Keywords: cyborgs; cyborgization; new eugenics; transhumanism; education; eugenics; future of education